Studentsâ Perceptions on Professional Competence of Lecturers at the Department of Arabic Education, Faculty of Islamic Education and Teacher Training, State Institute for Islamic Studies IB Padang - Rehani, Rehani (AT-TALIM, 2015)
This research examines studentsâ perception on professional competence of Arabic education department lecturers. It seeks to answer questions whether or not educational background, level of education, age, and gender correlate with lecturersâ professional competent. In this study, students are asked to answer questions on their lecturersâ 1) mastery of subject matters, 2) pedagogical knowledge, 3) attitudes, 4) discipline, 5) clarity on the assessment procedure, 6) the use of teaching media and studentsâ learning achievement. The findings of the study suggest that over 50% of students perceive their lecturers (those who teach in department of Arabic Education) are qualified enough to carry out their professional responsibilities. The research also uncovers that lecturersâ background education, such as between those who graduated from local and overseas universities, does not show any significant difference in their ways of classroom practices. However, the research found that level of education indeed influences lecturerâs ways of teaching, especially on the aspects that become the focus of this research. In addition, age does not show much different but in some instances, senior lecturers are more capable at pedagogical content knowledge, assessment, and better of in term of the attitude. Finally, this research also found that gender difference does make difference. Female lecturers, for example are found to be better in all aspects measured for this study.Â Â Copyright Â© 2015 by Al-Talim All right reserved